Vancomycin-loaded silk fibroin microspheres in an injectable hydrogel for chronic osteomyelitis therapy - Zhang, Peng; Sun, Yusheng; Yang, Haizhen; Liu, Dong; Zhang, Feng; Zhang, Yu; Zhong, Wentao; Zuo, Baoqi; Zhou, Zhiqiang (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract: Chronic osteomyelitis, often resulting in avascular necrosis and accumulation of dead bone tissue, remains a clinical challenge in orthopedics. The commonly used treatment composed of antibiotics and polymethyl methacrylate (PMMA) has several disadvantages, including fast drug release and lack of bone regeneration. In this study, silk fibroin microspheres (SFMPs) loaded with vancomycin are entrapped in an injectable silk hydrogel to form a vancomycin delivery system for the treatment of chronic osteomyelitis. The release features of vancomycin from SFMPs and hydrogel are assessed in vitro at two different pH values. Vancomycin showed continuous release from the hydrogel for up to 25 days, and the release behavior is affected by the vancomycin concentration, pH value, and the combination of SFMPs and hydrogel. Evaluated using an antibacterial zone assay, the hydrogel shows strong antibacterial activity against both Escherichia coli and Staphylococcus aureus and a long antibacterial duration of 10 days without a decrease in the antibacterial effect. In addition, the nontoxicity of the composite hydrogel is confirmed by MTT assay. The injection of vancomycin-loaded SFMPs entrapped in hydrogel into the infected site of rat tibia achieves reduced bone infection and improved bone regeneration compared with other treatment groups. In conclusion, the SF microspheres in the injectable SF hydrogel feature a sustained release profile and good biocompatibility, making this delivery system promising for application in osteomyelitis treatment.